Olive mill waste bio-based catalyst application in advanced oxidation processes for wastewater treatment - Rocha, Kleper O.; Brandão, Francisco; Mendes, C.átia; Carvalho, Maria G.V.S.; Mazierski, Paweł; Zaleska-Medynska, Adriana; Gomes, João; Martins, Rui C.; Domingues, Eva (Catalysis today, 2024)
This study explores the physicochemical capacities of solid wastes from olive oil mills (olive stone, OS, and olive pomace, OP), in obtaining catalysts to be applied in heterogeneous Fenton and persulfate processes. Through physicochemical treatments and the impregnation of iron by hydrothermal deposition and wetness impregnation (WI) different catalysts were produced, tested and characterized. The olive mill wastewater (OMW) studied in this work is a synthetic solution with five phenolic compounds to mimic the real effluent. The removal efficiency of phenolic acids and organic load (COD) present in this type of effluent was evaluated. In the treatment of synthetic wastewater, almost 100% COD was removed using OS and OP-FeWI as catalysts in the heterogeneous Fenton process. In the sulfate radical-based reaction, the 3,4–Dihydroxybenzoic acid was slightly more degradable than other phenolic acids which confirms the selectivity of sulfate radicals. The materials subject to thermal processes revealed an interesting adsorption capacity. This procedure not only reduces the environmental impact of OMW, but also promotes the implementation of new circular economy approaches. [Display omitted] •Olive mill waste can be suitable used for the preparation of iron catalysts.•Incipient wetness and hydrothermal impregnation were used for Fe catalyst preparation.•Fenton process almost reduces all initial chemical oxygen demand from simulated olive mill wastewater.•Olive mill waste biochar with incipient wetness Fe impregnation is the better adsorbent.